MODEL-MODEL PENGELOLAAN ZAKAT DI DUNIA MUSLIM - K., Amiruddin (Ahkam: Jurnal Hukum Islam, 2015)
Role of civil society and government in managing zakah can be conductedby coordinatively and actively. The role of goverment as giving politicallegitimation and data sourcer in developing zakah while the institution ofzakah organizer of civil society acts as excecutive in collecting and managingzakah. The relationship of both is conducted sinergictly and has direct accesseach other coordinatively or controlly.In practice, civil society is shaped invertical and horizontal coordination, in which vertical coordination is heldby holding company in controlling the processes of collecting and distributingzakah at organizations that responsible for doing that. On the other hand,horizontal coordination is aimed to create a cooperation among institutions.Such model of cooperation reflects an active involvement of civil society, andcould strengthen the function of civil society and government.Kata kunci: Model Pengelolaan Zakat, Dunia Muslim